Effects of Glycerol Monooleate on Improving Quality Characteristics and Baking Performance of Frozen Dough Breads - Haocheng Liu; Jiguo Yang; Yujuan Xu; Jing Wen; Jinfeng Zhou; Zhijie Xu; Jian Li; Xueke Sun; Weili Si (Foods)
This study investigated the impact of glycerol monooleate (MO) at varying levels (0.3%, 0.6%, 0.9%, and 1.2%) on the quality and baking properties of frozen dough. Low-field NMR and MRI were used to analyze the moisture distribution, water migration, and structural changes during frozen storage. The results indicated that MO reduced the content of free water, leading to a decrease in the spin–spin relaxation time of free water (T23). At the same time, the increase in the content of bound water resulted in an increase in the spin–spin relaxation time of bound water (T21). Rheological and SEM analyses revealed that MO preserved the dough’s microstructure and improved its rheological properties, reducing mechanical damage and inhibiting free water crystallization. This study found that by 8 weeks of frozen storage, the frozen dough containing 0.6% MO exhibited the best fermentation performance, with a larger fermentation volume and specific volume, and lower bread hardness, measuring 80 mL, 3.48 mL/g, and 1.10 N, respectively. These findings highlight MO’s potential in terms of enhancing frozen dough quality by maintaining the moisture balance and structural integrity during storage, offering a practical approach to improving bakery product quality.